PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM ORGANISASI TERHADAP EMPLOYEE ENGAGEMENT SERTA DAMPAKNYA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Lalu Jagat Firman Hadinata; Surati Surati; Lalu Suparman (Master of Management, Mataram University, 2019)
This study examines the effect of transformational leadership style and organizational climate on employee engagement and OCB on NTB Provincial Secretariat staff. Specifically the purpose of this study was to determine the significance of the influence of transformational leadership style, organizational climate and employee engagement on employee OCB, find out the significance of the influence of transformational leadership style and organizational climate on employee engagement, as well as knowing the mediating role of employee engagement variables in Provincial Regional Secretariat employees NTB. The population of this study was all employees who served in the NTB Provincial Secretariat were 378 respondents. There were 237 questionnaires that were received back or the questionnaire return rate was very high because it reached 62.70 percent, then the data collected was further analyzed. This research uses structural equation modeling (SEM analysis) with AMOS applications. The results showed that transformational leadership style and employee engagement had a significant positive effect on OCB, while organizational climate did not significantly influence OCB. Transformational leadership style and organizational climate have a significant positive effect on employee engagement. For the mediation effect of employee engagement, there is a full mediating role in the influence of transformational leadership styles and organizational climate on OCB.Keywords :Transformational Leadership Style, Organizational Climate, Employee Engagement, OCB.